2021
DOI: 10.1096/fj.202002113r
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Jak1 activation provokes hepatic inflammation and imbalanced FGF23 production and cleavage

Abstract: Fibroblast growth factor 23 (FGF23) is a main regulator of mineral homeostasis. Low and high circulating FGF23 levels are associated with bone, renal, cardiovascular diseases, and increased mortality. Understanding the factors and signaling pathways affecting FGF23 levels is crucial for the management of these diseases and their complications. Here, we show that activation of the Jak1/Stat3 signaling pathway leads to inflammation in liver and to an increase in hepatic FGF23 synthesis, a key hormone in mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 56 publications
7
28
0
Order By: Relevance
“…Our previous studies found that calcitriol is elevated in mice following Jak1/Stat3 activation 26 . Here, we confirmed these changes using another independent group of mice (Figure 1A).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our previous studies found that calcitriol is elevated in mice following Jak1/Stat3 activation 26 . Here, we confirmed these changes using another independent group of mice (Figure 1A).…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, MAP kinase signaling plays a major role in bone formation and remodeling, 35,50,51 and we showed here that systemic Jak1/Stat3 activation led to lower Erk1/2 activation in bone. Moreover, we observed that Il‐6 expression is higher in long bones after Jak1/Stat3 activation indicating local inflammation, as observed previously in the liver 26 . As mentioned previously, Il‐6 (and Il‐1) had been reported to increase osteoclast differentiation, 16,17 and may play a role in the alterations observed here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…7 The emerging evidence shows that the activation of JAK1/STAT3 signaling pathway leads to liver inflammation and liver fat deposition, which can significantly increase the synthesis of FGF23 in the liver, suggesting a bidirectional effect between liver fat deposition and FGF23. 37 To the best of our knowledge, this is the first study of the associations of serum FGF23 level and MAFLD. However, this study had a few limitations.…”
Section: Discussionmentioning
confidence: 88%
“… 7 The emerging evidence shows that the activation of JAK1/STAT3 signaling pathway leads to liver inflammation and liver fat deposition, which can significantly increase the synthesis of FGF23 in the liver, suggesting a bidirectional effect between liver fat deposition and FGF23. 37 …”
Section: Discussionmentioning
confidence: 99%